Short-term transplantation effect of a tissue-engineered meniscus constructed using drilled allogeneic acellular meniscus and BMSCs - Dai, Pengxiu; Zou, Tong; Zhao, Wen; Lv, Yangou; Gao, Dengke; Ruan, Chenmei; Zhang, Xia; Zhang, Xinke; Zhang, Yihua (Frontiers in Veterinary Science, 2023)
During the construction of tissue-engineered meniscus, the low porosity of extracellular matrix restricts the flow of nutrient solution and the migration and proliferation of cells, thus affecting the tissue remodeling after transplantation. In this study, the canine allogeneic meniscus was drilled first and then decellularized. On the basis of ensuring the mechanical properties, the number of the porosity and the cells implanted in allogeneic acellular meniscus was significantly increased. The expression levels of glycosaminoglycans and type II collagen in the drilled tissue-engineered meniscus (Drilled Allogeneic Acellular Meniscus + Bone Marrow Mesenchymal Stem Cells, BMSCs) were also improved. The drilled tissue-engineered menisci were transplanted into the knee joints of model dogs. It was determined that the animals in the experimental group recovered well compared with those in the control group. The graft surface was covered with new cartilage, the retraction degree was small, and the tissue remodeling was good. The surface wear of the femoral condyle and tibial plateau cartilage was light. The results of this study showed that increasing the porosity of allogeneic meniscus by drilling could not only maintain the mechanical properties of the meniscus and increase the number of implanted cells but also promote cell proliferation and differentiation. After transplantation, the drilled tissue-engineered meniscus provided a good remodeling effect in vivo and played a positive role in repairing meniscal injury, protecting articular cartilage and restoring knee joint function.